Environment, Local Society and Sustainable Tourism - Jokimäki, Jukka (ed.); Kaisanlahti-Jokimäki, Marja-Liisa (ed.); Tuulentie, Seija (ed.); Laine, Kari (ed.); Uusitalo, Marja (ed.) (Lapin yliopisto, Arktinen keskus, 2007)
v ok